Empire as material setting and heuristic grid for New Testament interpretation: Comments on the value of postcolonial criticism - Punt, J. (HTS teologiese studies, 2010)
Using postcolonial analysis to account for the Roman Empire’s pervasive presence in and influence on early Jesus-follower communities (early Christians), as depicted in New Testament texts, is both evident (given its usefulness for analysing situations of unequal power relationships) and complicated. The complications are due partly to the material and conceptual potential and constraints inherent in postcolonial biblical studies, as well as to the complexities involved in dealing with empire and imperialism. The study of the Roman Empire, as far as its impact on early Christianity and (in this article) on the letters of Paul is concerned, requires attention to Empire’s material manifestation, ideological support for Empire, and religious aspects – issues that are identified and briefly discussed. Empire can be understood in many different ways, but it was also constantly constructed and negotiated by both the powerful and the subjugated and therefore attention is required for its possible reach, uses and the purposeful application of discursive power in New Testament texts that were contemporary with Empire.